Israeli-Palestine Conflict : Compromise and Restraint Needed - Ong, Keng Yong (2017)
Washington’s controversial recognition of Jerusalem as the capital of Israel has refocused attention on the long-running dispute between the Israelis and the Palestinians, who see the eastern part of the city as the capital of their future state. Singapore must patiently and skilfully manage its relations with both sides.